Cancel Culture als Arena politisierter Wissenskonflikte Am Beispiel einer Debatte um rassistische Begriffe im Sommer 2022 - Richter, Susanne (Verhandlungen des 41. Kongresses der Deutschen Gesellschaft für Soziologie in Bielefeld 2022)

Turning Disciplinary Differences from a Brake into a Motor in Higher Education (Collaboration) - Sloane, Hannah Sabrina; Schmöckel, Sabrina

First steps towards real-time assessment of attentional weights and capacity according to TVA - Banh, Ngoc Chi; Scharlau, Ingrid (Abstracts of the 65th TeaP)

"ProGRess" - Erste Evaluationsergebnisse eines Anti-Prokrastinationstrainings auf Basis des Zürcher Ressourcen Modells (ZRM). - Schneider, Tamara; Klingsieck, Katrin B.

"ProGRess" - Reduce procrastination to improve students' health - First analyses of an intervention study. - Schneider, Tamara; Klingsieck, Katrin B.

Framing Goals of Mathematics Support Measures - Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Schürmann, Mirko; Biehler, Rolf; Schaper, Niclas (Practice-Oriented Research in Tertiary Mathematics Education)

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 10,2: Zettelsammlung aus den Synopsen der Manuskriptbände I bis X, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2023, xv, 229–475 S - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete, Zbl. 1527.01035)

Du Châtelet et la tradition critique de la Bible. De la ‘philofolie’ aux Examens - Hagengruber, Ruth Edith (La Lettre clandestine n° 30: Émilie Du Châtelet et la littérature clandestine. Moreau, P.F. & Seguin, M.S. (Eds.). Paris)

Knowledge Equity and Open Science in qualitative research – Practical research considerations - Steinhardt, Isabel; Kruschick, Felicitas (Research Ideas and Outcomes)
How can Knowledge In/Equity be addressed in qualitative research by taking the idea of Open Science into account? Two projects from the Open Science Fellows Programme by Wikimedia Deutschland will be used to illustrate how Open Science practices can succeed in qualitative research, thereby reducing In/Equity. In this context, In/Equity is considered as a fair and equal representation of people, their knowledge and insights and comprehends questions about how epistemic, structural, institutional and personal biases generate and shape knowledge as guidance. Three questions guide this approach: firstly, what do we understand by In/Equity in the context of knowledge production in these projects? Secondly, who will be involved in knowledge generation and to what extent will they be valued or unvalued? Thirdly, how can data be made accessible for re-use to enable true participation and sharing?
Keywords: Open Science; Knowledge Equity; Qualitative Methods

Die „dritte Wissensdimension“. Eine Epistemologie für eine neue Wissenswelt - Hagengruber, Ruth Edith (Sitzungsberichte der Leibniz-Sozietät der Wissenschaften 150/151, Jahrgang 2022: „Cyberscience – Wissenschaftsforschung und Informatik. Digitale Medien und die Zukunft der Kultur wissenschaftlicher Tätigkeit. Arbeitskreis „Emergente Systeme/Informatik und Gesellschaft“ der Leibniz-Sozietät der Wissenschaften zu Berlin in Kooperation mit der Gesellschaft für Wissenschaftsforschung“)

Transitivitätscharakteristika als Werkzeug in der systematischen qualitativen Metaphernanalyse - Karsten, Andrea; Schwede, Jana; Körber, Miriam; Scharlau, Ingrid (Die Praxis der systematischen Metaphernanalyse)

Kollaborative Autoethnographien digitaler Praktiken. Eine konzeptionelle, methodische und theoretische Einführung zu einem Lehr-Forschungsprojekt im ersten Corona-Semester - Steinhardt, Isabel (DNGPS Working Paper)
Keywords: Open Science; kollaborative Autoethnographie

Hundertstelmillimeter - Scharlau, Ingrid (Reflexive Schreibwissenschaft)

Reflexive Schreibwissenschaft

Du Châtelet and Kant: Claiming the Renewal of Philosophy - Hagengruber, Ruth Edith (Époque Émilienne)
n 1789, Eberhard repudiated Kant’s claim expressed in the first edition of his Critique of Pure Reason to have delivered a new, namely transcendental turn in philosophy, as he was able to retrace our cognition to the origin of phenomena instead of delivering a “merely logical deduction”. Eberhard holds that there was nothing new, but all delivered in Leibniz and Wolff; to prove his claim he refers to a quote from Du Châtelet, taken from a paragraph where she determines the right understanding as to be able “to penetrate to the origin of phenomena”. This paper brings Du Châtelet into discourse with Kant via this Eberhard quote. In its first part, it investigates the use of her quote in the Kant-Eberhard controversy. The second part serves to ground the quote in Du Châtelet’s epistemology. It lays out how to understand Du Châtelet’s claim to penetrate to the origin of phenomena. Du Châtelet’s claim to have renewed philosophy must be taken seriously, and it is helpful for rethinking the German philosophical development from the rationalists to Kant through including Du Châtelet’s theory of cognition.
Keywords: Émilie Du Châtelet; History of Science; Newton; Kant; Eberhard; Wolff; Leibniz

Époque Émilienne
Keywords: Émilie Du Châtelet; History of Science; Kant; Newton; Maupertuis; Voltaire

Knowledge Equity and Open Science in qualitative research – Practical research considerations - Steinhardt, Isabel; Kruschick, Felicitas (Research Ideas and Outcomes)
How can Knowledge In/Equity be addressed in qualitative research by taking the idea of Open Science into account? Two projects from the Open Science Fellows Programme by Wikimedia Deutschland will be used to illustrate how Open Science practices can succeed in qualitative research, thereby reducing In/Equity. In this context, In/Equity is considered as a fair and equal representation of people, their knowledge and insights and comprehends questions about how epistemic, structural, institutional and personal biases generate and shape knowledge as guidance. Three questions guide this approach: firstly, what do we understand by In/Equity in the context of knowledge production in these projects? Secondly, who will be involved in knowledge generation and to what extent will they be valued or unvalued? Thirdly, how can data be made accessible for re-use to enable true participation and sharing?
Keywords: Open Science; Knowledge Equity; Qualitative Methods

Die (Un-)Sichtbarkeit von (offenen) Bildungsmaterialien in der Soziologie - Hiebl, Johannes; Steinhardt, Isabel; Bigos, Michael (die hochschule)
Der Beitrag beschäftigt sich mit dem Gebrauch von sogenannten Open Educational Resources (OER) innerhalb der deutschsprachigen Soziologie. OER sind Lehr-und Lernmaterialien, die öffent-lich und frei von Kosten zugänglich sind sowie unter einer offenen Lizenz stehen, die es erlaubt, das Material frei zu nutzen, zu vervielfältigen und zu bearbeiten. Um diese Form der Bereitstellung von Lehr-und Lernmaterial zu fördern, sind im deutschen Sprachraum in den letzten Jahren verschie-dene digitale Infrastrukturen entstanden, die an einzelnen Hochschulstandorten, aber auch hochschulübergreifend Lehrenden zur Verfügung stehen, um dort ihr Material zu veröffentlichen. Es wurden 37 dieser Repositorien untersucht. Darüber hinaus wurde auch die Videoplattform YouTube nach soziologischem Lehr-und Lernmaterial durchforstet. Der Beitrag stellt den Zeitverlauf und die Akteur:innen der OER-Veröffentlichungen dar. Anschließend soll mithilfe eines praxistheoretischen Vokabulars die Lehre innerhalb der Soziologie aufgeschlüsselt und ein möglicher Bezug zu den empirischen Ergebnissen hergestellt werden.
Keywords: Soziologie; Praxistheorie; Repositorien; Open Educational Resources; OER

Dem eigenen Anspruch auf der Spur - Ternes, Doris; Bernhard, Nadine; Gewinner, Irina; Goller, Antje; Lohner, David; König, Karsten; Röwert, Ronny; Steinhardt, Isabel; Thielsch, Angelika (Hochschulen in der Pandemie. Impulse für eine nachhaltige Entwicklung von Studium und Lehre)
Der Beitrag geht der Frage nach, welchen Herausforderungen Lehrende durch die digitale Lehre im ersten Corona-Semester 2020 begegnet sind und welche Strategien sie für deren Bewältigung gewählt haben. Als Datengrundlage dienendazu sechs autoethnographische Stories, entstanden im Projekt AEDiL. Diese haben sich als wertvolles Material erwiesen, um unmittelbare Einblicke in das Lehrhandeln und die -planung zu erhalten und die weiterführende Analyse zu ermöglichen. Dabei offenbarte sich der gemeinsame Anspruch der studierenden-zentrierten Lehre als wiederkehrendes Muster. Die mehrstufige Analyse legt offen, wie Lehrpersonen mit den Themen Beziehungsaufbau, Schaffung eines (digitalen) Raums sowie Sicherheit für Studierende umgehen und sich daraus Handlungsmuster entwickeln.

Language in the Age of Mechanical Reproduction - Thomas, Sven (Technology and Language)

Luna, Laureano. “Strengthening the Russellian Argument Against Abolutely Unrestricted Quantification”. Synthese 200 (2022), No. 3, Paper No. 182, 13 pp - Peckhaus, Volker (Mathematical Reviews)

Toward a Competence Model for Graphical Modeling - Soyka, Chantal; Schaper, Niclas; Bender, Elena; Striewe, Michael; Ullrich, Meike (ACM Transactions on Computing Education)
Modeling is an integral part of many computing-related disciplines and thus also represents a curricular core component in computing education in tertiary education. Competence models in which modeling is integrated at least to some extent already exist in some of these disciplines. However, for the core component of graphical modeling, a competence model that illuminates the relevant competences in detail is still lacking. Therefore, we develop a competence model for graphical modeling with the aim to make teaching and especially assessments in the field more competence-oriented. This paper reports on the first two studies conducted to develop and validate the competence model for graphical modeling. In the first study, the structure of the competence model was developed based on theories and approaches of educational science. Competences relevant for graphical modeling were deductively derived from literature and existing university course descriptions using techniques of qualitative content analysis. The result of the first study is a preliminary competence model. In the second study, the preliminary competence model was reviewed by means of an expert rating in the modeling community. The competence model was revised and refined based on these findings and subsequent expert discussions. The main result of the investigation represents the competence model for graphical modeling (CMGM), which includes a total of 74 competence facets at different cognitive process levels in the five content areas of ”model understanding and interpreting”, ”model building and modifying”, ”values, attitudes, and beliefs”, ”metacognitive knowledge and skills”, and ”social-communicative skills”.
Keywords: graphical modeling; conceptual modeling; computer science; competence model; higher education

Piloteinsatz einer E-Assessment-Plattform für die grafische Modellierung - Ullrich, Meike; Pfeiffer, Peter; Schiefer, Gunther; Soyka, Chantal; Stottrop, Tobias; Striewe, Michael; Fettke, Peter; Loos, Peter; Oberweis, Andreas; Schaper, Niclas (20. Fachtagung Bildungstechnologien (DELFI))

E-Assessment-Plattform für die grafische Modellierung - Ullrich, Meike; Pfeiffer, Peter; Schiefer, Gunther; Soyka, Chantal; Stottrop, Tobias; Striewe, Michael; Fettke, Peter; Loos, Peter; Oberweis, Andreas; Schaper, Niclas (20. Fachtagung Bildungstechnologien (DELFI))

Informal Workplace Learning at a Glance: Validation of Short Measure for White-Collar Workers. - Decius, Julian; Knappstein, Michael; Schaper, Niclas; Seifert, Andreas (European Association of Work and Organizational Psychology Congress 2022.)

Off Your Own Bat or Aided by Others: A Vignette Study on the Role of Metacognitions and Social Support for Informal Workplace Learning. - Decius, Julian; Knappstein, Michael; Seifert, Andreas (Hawaii International Conference On Education.)

Off Your Own Bat or Aided by Others? An Investment-Reward Typology of Metacognition and Social Support at Work. - Seifert, Andreas; Decius, Julian; Knappstein, Michael (EARLI SIG14 Conference)

Effects of Digital Transformation on Job Satisfaction and Employee Retention: An Integrative Framework - Depenbusch, Sarah; Schürmann, Mirko; Schaper, Niclas; Seifert, Andreas; Schumacher, Jan-Philip; Straatmann, Tammo

Digitaler Wechselunterricht in der gymnasialen Oberstufe – ein Modell mit Zukunft? - Rogge, Tim; Seifert, Andreas (AEPF-Tagung „Lehren und Lernen neu gedacht – Konsequenzen für das zukünftige Bildungswesen“)

Pädagogische Kompetenz als Ausgangspunkt beruflichen Könnens!? Ergebnisse der Kompetenzmessung angehender Lehrkräfte unter Berücksichtigung individueller Voraussetzungen. - Caruso, Carina; Seifert, Andreas (Religionspädagogische Beiträge. Journal for Religion in Education.)

Validierung von Testinstrumenten durch Testmotivationsindikatoren. - Watson, Christina; Meier, Jana; Seifert, Andreas; Küth, Simon; Scholl, Daniel (DGPs-Tagung „View on of Science“, Hildesheim)

Inwiefern ist die Professionalisierung in Praxisphasen schulformspezifisch? Ergebnisse der Messung pädagogischer Kompetenzen Studierender in Deutschland. - Caruso, Carina; Seifert, Andreas (Österreichisches Religionspädagogisches Forum)

Participative human-factor evaluation in the context of digital work (re-)design - Schumacher, Jan-Philip; Depenbusch, Sarah; Straatmann, Tammo; Bender, Elena; Schaper, Niclas; Hamborg, Kai-Christoph (Work)
BACKGROUND: Challenged by digital transformation, organizations increasingly integrate information and communication technologies into work designs. Often focal points of such digital reengineering initiatives are technical and economic aspects. Yet, as integration of new technologies affects how employee work and interact, there is a need to evaluate human-centered criteria (human-factor evaluation), optimally by involving employees as situational experts. OBJECTIVE: The present study develops an integrative and persona-based evaluation approach of human-centered criteria for application in participative digital (re-)design of work to support the joint optimization of the technical and social system. METHODS: Drawing on methods from usability evaluation, a persona-based approach is developed to facilitate comprehension and application of human-centered evaluation by employees. To that end, human-centered criteria from existing evaluation models are systemized with specific reference to digital transformation of work processes. The developed approach is tested in pilot runs of three German small and medium-sized enterprises (SMEs). RESULTS: The initial overview shows a divergence of specific human-centered criteria at the detailed level. Simultaneously, a high convergence is found for overarching dimensions and categories. The Integrative Socio-Digital Evaluation Model (ISDEM) is developed to balance complexity and abstraction of criteria. The derived persona-based approach (persISDEM) shows a good applicability in the pilot runs. CONCLUSIONS: The present study provides an amendment to existing work design approaches with an emphasis on employee participation, enabling organizations to foster employees’ comprehension and motivation to engage in evaluations of digital (re-)design of work and to create motivating and healthy jobs for successful digital transformation.
Keywords: Public Health; Environmental and Occupational Health; Rehabilitation

Qualitätssicherung im bildungswissenschaftlichen Studium – methodologische Überlegungen. - Seifert, Andreas; Watson, Christina (DGPs-Tagung „View on of Science“)

Förderung von motivierenden Gesprächsstrategien im Elterngespräch. Workshop für Lehrkräfte und Studierende - Hilkenmeier, Johanna; Greiner, Christian; Bonanati, Sabrina; Buhl, Heike M. (Journal für LehrerInnenbildung)

(Be)Werten im organisationsabhängigen Interaktionssystem: das Beispiel Peer Review in Akkreditierungsverfahren von Hochschulen und Studiengängen - Schneijderberg, Christian; Götze, Nicolai; Steinhardt, Isabel; Schindler, Janosch (Zeitschrift für Evaluation)
In diesem Beitrag wird die ‚What Works‘-Debatte in der Sozialen Arbeit um die zentrale Frage nach Wirkfaktoren erweitert. Der empirische Nachweis von Wirkfaktoren in sozialarbeiterischen Interventionen ist bis heute ein Desiderat. Vor dem Hintergrund der Realist Evaluation werden in diesem Beitrag relevante Wirkfaktoren (Kontexte und Mechanismen) herausgearbeitet. Datengrundlage stellt eine Onlinebefragung von 200 fallführenden Fachpersonen in vier sozialarbeiterischen Handlungsfeldern in der deutschsprachigen Schweiz dar (Arbeitsintegration, Bewährungshilfe, Schuldnerberatung, Sozialhilfe). Die Ergebnisse verweisen auf signifi kante Wirkfaktoren von erfolgreichen Interventionen, u.a. Arbeitsstile der Fachpersonen und Verhaltensmerkmale der Klient(inn)en und können in einem allgemeinen Wirkungsmodell mit handlungsfeldübergreifenden Outcomes verdichtet werden. Diese Erkenntnisse leisten einen Beitrag zur Professionalisierung der Sozialen Arbeit sowie zur Konstruktion von Wirkungsmodellen und sollen zukünftige weitere Forschungsvorhaben in diese Richtung anregen.
Keywords: Soziologie des Wertens und Bewertens; Peer Review; Akkreditierung; Hochschule

Effects of verbal negation on TVA’s capacity and weight parameters - Banh, Ngoc Chi; Scharlau, Ingrid (TeaP 2022 - Abstracts of the 64th Conference of Experimental Psychologists)

Folgen wiederholter Negation auf die Aufmerksamkeit - Banh, Ngoc Chi; Scharlau, Ingrid; Rohlfing, Katharina J. (52. Kongress der Deutschen Gesellschaft für Psychologie)

Gesundes Misstrauen gegenüber Erklärungen - Peters, Tobias Martin; Scharlau, Ingrid (52. Kongress der Deutschen Gesellschaft für Psychologie)

Die Förderung von Reflexionskompetenz und Reflexion durch die angeleitete Bearbeitung eines weiterentwicklungsorientierten Online-Self-Assessments - Buhl, Heike M.; Sagolla, Nils; Bohndick, Carla (Lehrerbildung auf dem Prüfstand)

Eingeschrieben und Geblieben. Herkunftsgruppenspeziﬁsche Bedingungen des Studienverbleibs nach der Studieneingangsphase an Universitäten. - Mauermeister, Sylvi
Hochschulische Bildungsverläufe und -erfolge sind in Deutschland anhaltend maßgeblich von der sozialen Herkunft beeinflusst. Gleichzeitig bestehen Anforderungen an moderne Gesellschaften, Unterschiede in den bildungsbezogenen Chancen abzuschaffen, die nicht aus Leistungsunterschieden, sondern aus der Zugehörigkeit zu bestimmten sozialen Gruppen resultieren. Auch angesichts der hohen Bedeutung der Studieneingangsphase für den Studienerfolg stellt sich die Frage, wie sich Unterschiede in den ökonomischen und kulturellen Ressourcen der Herkunftsfamilie auf den Verlauf der Studieneingangsphase auswirken. Welche Unterschiede zeigen sich in den Bedingungen des Studienverbleibs, der Ausstattung mit studienverbleibsrelevanten Ressourcen und dem Umgang mit Problemen? Die Untersuchung zeigt vor allem zweierlei: Zum einen sind die Schwierigkeiten mit den universitären und fachspezifischen Bedingungen, die bereits nach dem ersten Studiensemester sichtbar werden, stark abhängig von der Fächergruppe, in der studiert wird. Zum anderen ist für das Gelingen der Studieneingangsphase das kulturelle Kapital der Herkunftsfamilie von größerer Bedeutung als das ökonomische Kapital. Die Ergebnisse sind gleichermaßen für die Bildungs- wie die Ungleichheitsforschung relevant und erlauben es, Handlungsoptionen zur Gestaltung der Studieneingangsphase abzuleiten.

Paralleluniversen des Wissenschaftsmanagements: Ein Vergleich zwischen Hochschulen und außeruniversitären Forschungseinrichtungen. - Schneider, Sebastian; Mauermeister, Sylvi; Aust, Robert; Henke, Justus

Von lebenden Systemen und gefühlten Zahlen. Eine körpersoziologische Analyse des finanzaufsichtlichen Risikobewertungsregimes - Knoll, Lisa (Österreichische Zeitschrift für Soziologie)
Der hier vorliegende Beitrag erarbeitet Verbindungslinien zwischen Wirtschaftssoziologie (insb. Finanzsoziologie), Soziologie der Bewertung und Körpersoziologie anhand des Falls finanzmarktregulatorischer Risikobewertung. Dabei spielt der analytische Begriff der Prothese (Michel Callon) eine wichtige Rolle. Nach der Finanzkrise kommt es zu einer Neuverteilung von sensorischen Bewertungskompetenzen in einer hierarchisch aufgebauten, vernetzten Wissensarchitektur. Es ist nun die Maschine, der Lebendigkeit attestiert wird, während der Mensch parzellierte Funktionen in einer Apparatur übernimmt. Gleichzeitig soll der Mensch so zu einem adäquaten und beweglichen (spielerischen) Umgang mit Risiken angeregt werden, die man ihm/ihr in einem eher groben und einfachen Aufsichtssystem nicht mehr zutraute (hier wurden „regulatory arbitrage“ und „kreative Buchführung“ zum Problem). Der Aufsatz rekonstruiert die praktischen Orientierungen und kollektiven Erfahrungen dieses finanzaufsichtlichen Umbaus anhand zweier problemzentrierter Interviews. Unter Rekurs auf die Körperbezüge in diesen Interviews wird die Paradoxie eines Systems herausgearbeitet, das nach wie vor auf individuelle Entscheidungsrationalität und -agilität setzt, diese nun aber maschinell zu erschaffen sucht.
Keywords: General Social Sciences

Contested Social Impact Bonds: welfare conventions, conflicts and compromises in five European Active-Labor Market Programs - Fraser, Alec; Knoll, Lisa; Hevenstone, Debra (International Public Management Journal)
Keywords: Public Administration; Business and International Management

Die EU-Taxonomie für nachhaltige Finanzen: Auf dem Weg in den grünen Kapitalismus? - Knoll, Lisa (Kapitalismus und Nachhaltigkeit)
Keywords: Klima

Parental involvement and Children's internet uses - Relationship with parental role construction, self-efficacy, internet skills, and parental instruction - Gruchel, Nicole; Kurock, Ricarda; Bonanati, Sabrina; Buhl, Heike M. (Computers & Education)
Internet use is significant in the everyday lives of children and can be distinguished into different uses (e.g., entertainment-related, informative or school-related). When considering the literature on internet inquiries, the family as an informal place of learning is of particular importance. Although some predictors within the family (e.g., structural factors) are widely researched, comprehensive results on the influence of parental involvement, especially parental instruction as a form of parental support during information-related internet activities, on different internet uses are still lacking. Therefore, the study investigates (1) the relationship of parental role construction, self-efficacy, internet skills, and parental instruction in information-related internet use perceived by parents and children and (2) the relationship of parental role construction, self-efficacy, internet skills, parental instruction, and children's internet uses at home (entertainment-related, practical and school-or-learning-related). The mediation effects of parental instruction were also tested. A paper-and-pencil questionnaire was answered by 361 German children and their parents. Structural equation modeling was applied to answer the research questions. We observed that children's perceived parental instruction was positively associated with children's practical and school-or-learning-related internet use. Parents' motivational factors were the strongest predictors for parents' perceived parental instruction The findings have significant implications for research and practice on how parents can be more active in fulfilling their role as supporters for children's internet use.

Procrastination Among University Students: Differentiating Severe Cases in Need of Support From Less Severe Cases - Rozental, Alexander; Forsström, David; Hussoon, Ayah; Klingsieck, Katrin B. (Frontiers in Psychology)
Procrastination refers to voluntarily postponing an intended course of action despite expecting to be worse off for this delay, and students are considered to be especially negatively affected. According to estimates in the literature, at least half of the students believe procrastination impacts their academic achievements and well-being. As of yet, evidence-based ideas on how to differentiate severe from less severe cases of procrastination in this population do not exist, but are important in order to identify those students in need of support. The current study recruited participants from different universities in Sweden to participate in an anonymous online survey investigating self-rated levels of procrastination, impulsivity, perfectionism, anxiety, depression, stress, and quality of life. Furthermore, diagnostic criteria for pathological delay (PDC) as well as self-report items and open-ended questions were used to determine the severity of their procrastination and its associated physical and psychological issues. In total, 732 participants completed the survey. A median-split on the Pure Procrastination Scale (PPS) and the responses to the PDC were used to differentiate two groups; “less severe procrastination” (PPS ≤ 2.99; n = 344; 67.7% female; M age = 30.03; SD age = 9.35), and “severe procrastination” (PPS ≥ 3.00; n = 388; 66.2% female; M age = 27.76; SD age = 7.08). For participants in the severe group, 96–97% considered procrastination to a problem, compared to 42–48% in the less severe group. The two groups also differed with regard to considering seeking help for procrastination, 35–38% compared to 5–7%. Participants in the severe group also reported more problems of procrastination in different life domains, greater symptoms of psychological issues, and lower quality of life. A thematic analysis of the responses on what physical issues were related to procrastination revealed that these were characterized by stress and anxiety, e.g., tension, pain, and sleep and rest, while the psychological issues were related to stress and anxiety, but also depression, e.g., self-criticism, remorse, and self-esteem. The current study recommends the PPS to be used as an initial screening tool, while the PDC can more accurately determine the severity level of procrastination for a specific individual.
Keywords: General Psychology

Delaying Academic Tasks and Feeling Bad About It - Bobe, Julia; Schnettler, Theresa; Scheunemann, Anne; Fries, Stefan; Bäulke, Lisa; Thies, Daniel O.; Dresel, Markus; Leutner, Detlev; Wirth, Joachim; Klingsieck, Katrin B.; Grunschel, Carola (European Journal of Psychological Assessment)
Abstract. Procrastination is the irrational delay of an intended task and is common among students. A delay can only be defined as procrastination when it is voluntary, the action was intended but not implemented, and the delay is accompanied by subjective discomfort. Established scales of procrastination cover mainly behavioral aspects but have neglected the emotional aspect. This inaccuracy concerning the construct validity might entail misconceptions of procrastination. Accordingly, we developed and validated the Behavioral and Emotional Academic Procrastination Scale (BEPS), which covers all aspects of the definition of procrastination. The 6-item scale measuring self-reported academic procrastination was tested in three studies. Study 1 ( N = 239) evaluated the psychometric qualities of the BEPS, indicating good item characteristics and internal consistency. Study 2 ( N = 1,441) used confirmatory factor analysis and revealed two correlated factors: one covering the behavioral aspect and the other reflecting the emotional aspect. Measurement invariance was shown through longitudinal and multigroup confirmatory factor analyses. Study 3 ( N = 234) provided evidence for the scale’s convergent validity through correlations with established procrastination scales, self-efficacy, and neuroticism. The BEPS thus economically operationalizes all characteristics of academic procrastination and appears to be a reliable and valid self-report measure.
Keywords: Applied Psychology

Wie können unterschiedliche Aspekte diagnostischer Kompetenz gefördert werden? - Grotegut, Lea; Klingsieck, Katrin B. (Zeitschrift für Pädagogische Psychologie)
Zusammenfassung. Eine gut ausgebildete diagnostische Kompetenz von Lehrpersonen ist eine wesentliche Voraussetzung für gelingenden Unterricht und trägt maßgeblich zur akademischen und persönlichen Entwicklung von Schülern bei. Häufig sind Lehrpersonen jedoch nur bedingt dazu in der Lage, Schülermerkmale wie Leistung, Motivation oder Ängstlichkeit adäquat zu beurteilen. Eine Förderung der diagnostischen Kompetenz sollte bereits während des Studiums stattfinden, um Lehrpersonen früh auf diagnostische Situationen in der Schulpraxis vorzubereiten und negative Konsequenzen möglicher pädagogischer Fehlentscheidungen zu vermeiden. Dieser Beitrag vergleicht eine lehrendenzentrierte, eine problembasierte und eine digitale, simulationsbasierte Maßnahme zur Förderung unterschiedlicher Aspekte diagnostischer Kompetenz an einer Stichprobe von N = 166 Lehramtsstudierenden im Hinblick auf ihre Wirksamkeit. Es zeigen sich insbesondere Vorteile der simulationsbasierten Fördermaßnahme in den Bereichen intrinsische Motivation und Interesse sowie Nachteile der lehrendenzentrierten Maßnahme im Bereich des Wissens um das systematische Vorgehen im diagnostischen Prozess und der problembasierten Maßnahme im Bereich des Extraneous Cognitive Load. Die Ergebnisse werden insbesondere im Hinblick auf ihre praktischen Implikationen im Rahmen der Lehrerbildung und zunehmend digitalisierter Lehre diskutiert.
Keywords: Developmental and Educational Psychology

Social factors of procrastination: group work can reduce procrastination among students - Koppenborg, Markus; Klingsieck, Katrin B. (Social Psychology of Education)
Abstract Research on procrastination covers a variety of individual factors (e.g., conscientiousness) and this focus is reflected in interventions against procrastination. Less emphasis is put on situational and social factors that may help students reduce procrastination, such as social interdependence. Therefore, this study investigates the relationship between interdependence with academic procrastination and affective variables. Two vignette studies with student samples ( N 1 = 320, N 2 = 193) were conducted and data was analyzed with regression analyses and analyses of covariance. Results of both studies show lower state procrastination in group work with interdependence compared to individual work, especially in participants with high trait procrastination. This difference is more pronounced when interdependence is accompanied by an active commitment to finish the task on time. Further, interdependent group work is related to increased positive affect and decreased negative affect. The results demonstrate the relevance of situational and social factors for academic procrastination, and point toward new approaches for intervention.
Keywords: Sociology and Political Science; Developmental and Educational Psychology; Social Psychology